2010
DOI: 10.1155/2010/201858
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bee Species and Plant Density on Alfalfa Pollination and Potential for Gene Flow

Abstract: In outcrossing crops like alfalfa, various bee species can contribute to pollination and gene flow in seed production fields. With the increasing use of transgenic crops, it becomes important to determine the role of these distinct pollinators on alfalfa pollination and gene flow. The current study examines the relative contribution of honeybees, three bumble bee species, and three solitary bee species to pollination and gene flow in alfalfa. Two wild solitary bee species and one wild bumble bee species were b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 26 publications
0
41
0
1
Order By: Relevance
“…Several native insects, including bumblebees ( Bombus ) and some solitary bees, can pollinate alfalfa (Cecen et al . ; Brunet & Stewart ). In seed‐production fields, honeybees ( Apis mellifera ) and alfalfa leafcutting bees ( Megachile rotundata ) are the most commonly used managed pollinators, while alkali bees ( Nomia melanderi ) are utilised in parts of the Pacific Northwest.…”
Section: Methodsmentioning
confidence: 99%
“…Several native insects, including bumblebees ( Bombus ) and some solitary bees, can pollinate alfalfa (Cecen et al . ; Brunet & Stewart ). In seed‐production fields, honeybees ( Apis mellifera ) and alfalfa leafcutting bees ( Megachile rotundata ) are the most commonly used managed pollinators, while alkali bees ( Nomia melanderi ) are utilised in parts of the Pacific Northwest.…”
Section: Methodsmentioning
confidence: 99%
“…This hypothesis is supported by a previous study in which seed set per tripped flower was similar for honey bees and leafcutting bees (Cane, 2002); therefore, the increase in seed set with more visits must result from more flowers being tripped and setting seeds. Female Megachile rotundata can trip 80% of the visited flowers (Pitts‐Singer and Cane, 2011), while tripping is much lower for the males (Cane, 2002), and the tripping rate is lower when external temperatures are cooler (Brunet and Stewart, 2010). Bumble bees are good trippers of Medicago sativa , with B. impatiens averaging a tripping rate of 45–55% (Holm, 1966; Brunet and Stewart, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Female Megachile rotundata can trip 80% of the visited flowers (Pitts‐Singer and Cane, 2011), while tripping is much lower for the males (Cane, 2002), and the tripping rate is lower when external temperatures are cooler (Brunet and Stewart, 2010). Bumble bees are good trippers of Medicago sativa , with B. impatiens averaging a tripping rate of 45–55% (Holm, 1966; Brunet and Stewart, 2010). Honey bees tend to exhibit low tripping rates unless temperatures are very high (Bohart, 1957; Cane, 2002), and they are known to avoid the tripping mechanism by stealing nectar from the sides of M. sativa flowers, which limits contact with the plant's sexual structures (Bohart, 1957).…”
Section: Discussionmentioning
confidence: 99%
“…Research focused on how foraging interactions between multiple species of commercial pollinators influence the movement of transgenic pollen would be beneficial. Also, research focused on pollen movement by native pollinators would be beneficial since previous research has indicated that they can be effective pollinators (Brunet and Stewart, 2010; Van Deynze et al, 2008). Producers of AP‐sensitive alfalfa seed have expressed concern that the movement of honey bee hives and leafcutting domiciles may contribute to the dispersal of genetically engineered pollen.…”
Section: Prevalence Of Practices and Perceptions That Support Or Undementioning
confidence: 99%